KELAYAKAN FLIPBOOK MATERI PERTUMBUHAN DAN PERKEMBANGAN KELAS XII SMA/MA DENGAN INFORMASI LAJU PERTUMBUHAN IKAN MAS (Cyprinus carpio L.) YANG DIBERI PAKAN BUATAN (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
The research aimed to explain the feasibility of the flipbook as a learning medium for the Material of Growth and Development in the twelfth grade of SMA/ MA based on the growth rate observation of Cyprinus carpio L. with artificial feed. We used a descriptive method which consisted of two stages, namely instrument and learning medium validation. The instrument was validated by two validators who were lecturers in Study Program of Biology Education of Tanjungpura University (Untan). The flipbook medium was validated by five validators consisting of two lecturers from Study Program of Biology Education and three biology teachers from three different high schools in Pontianak City. The instrument sheet consisted of three aspects and twelve criteria. Data were analyzed using content validity ratio (CVR) and content validity index (CVI) by Lawshe (1975). The results of flipbook media validation showed that all criteria obtained a CVR value of 0.99, therefore, the CVI value obtained was also 0.99. So, it can be concluded that the flipbook is declared valid and can be used as a learning medium for the Material of Growth and Development in the twelfth grade of SMA / MA.